Histopathological Features of Duodenal Coccidiosis in the Probiotic Broiler Chickens - Aven B Oematan; Damai Kusumaningrum (Jurnal Sain Veteriner, 2014)
This aim of research was to know histopathology lesions of broiler duodenum in chicken coccidiosis with probiotic administrasion. Sixty six DOC of broiler, strain Arbor acress, male sex were divided into 5 groups of twelve each. Chickens in Groups I, II, III, IV and V were given standard food, standard food+probiotic, standard food+1000 oocysts, standard food+probiotic+1000 oocysts and standard food+probiotic+ 3000 oocysts,respectively. Probiotic was given starting at the age of 8 days by sprayed in food with the dose 2 ml/ 250 ml water/ 1 kg food. At the age of 38 days, chickens were infected orally by given 1000 oocysts for group III and IV, and 3000 oocysts for group V. Group I and II were euthanazed at the age of 39 days, group IIIA, IVA, VA at 5 days postinfection, group IIIB, IVB, VB at 6 days post infection, and group IIIC, IVC, VC at 7 days post infection. Histopathologic lesions of the duodenums were analyzed with qualitative analyze. Results showed that infection without probiotic area were found histopathologic changes of duodenum in the form of congestion, hemorrhages, schizonts and macrogametes representing of Eimeria sp stadium which caused coccidiosis. Treatment infection with probiotic were found histopathologic changes in the duodenum, such as congestion,hemorrhages, necrotic epithelial cells, and also schizonts, microgametes and macrogametes representing of Eimeria sp stadium which caused coccidiosis. Probiotic in the present study did not have any effect for histopathologic changes in the duodenum in the broiler chickens infected coccidiosis.